Austriackie zabiegi o umowę ekstradycyjną z Rzecząpospolitą. 1786–1787 - Kordel, Jacek (Kwartalnik Historyczny, 2013)
Austrian Efforts for Achieving an Extradition Agreement with the Polish-Lithuanian Commonwealth. 1786–1787 The author discussed efforts pursued in 1786–1787 by the Viennese court and aimed at signing an extradition convention with the Commonwealth. Ostensibly, the object of the convention involved principles regulating the capture of criminals and army deserters. Actually, the Austrian side was concerned predominantly with the second part of the convention dealing with deserters and the unconstrained right of the Austrian troops to enter the territory of the Commonwealth in order to seek defectors. Sources serving as the foundation of the text include Austrian and Polish diplomatic correspondence, attached notes and other associated material. The author also used protocols of the Permanent Council and the latter’s Department of Foreign Interests as well as letters written by King Stanisław Augustus to Debole, the Polish minister in St. Petersburg and the monarch’s confidant. The negotiations conducted from April 1786 secretly and then openly by Primate Michał Poniatowski and Secretary of the Department of Foreign Interests Antoni Dzieduszycki ended in failure for the Austrians. In February 1787 the Permanent Council rejected the project prepared in Vienna and permitting incursions of Austrian soldiers into Polish territory. The Commonwealth did not intend to consent to such a restriction of sovereignty, this time for the sake of its southern neighbour. Equally important was the stand represented by Russia, which was uninterested in the presence of the Austrian army on Polish state territory, which it treated as a terrain of its exclusive impact.